Ia correction grammaticale, les anomalies sémantiques et la métaphore dans la grammaire transformationnelle-générative - Nkollo, Mikołaj (Studia Romanica Posnaniensia, 2007)
This paper deals mainly with the problem of semantic anomalies and their role in generative grammar. Once the issue was raised, the solutions brought about by authors varied among them considerably. As far as generative grammar is a formal theory, it cannot handle the anomalous uteerances with recourse to metaphor. Instead, two main approaches were proposed. The first one originates from a semantic theory set forth by Katz and Fodor and has been adopted by Chomsky and his followers. Its focus is laid on formal properties and technical aspects of the anomalies, without trying to explore their nature and their origin. The other one, argued for by the supporters of generative semantics, has resorted to extra-linguistic context and to one’s personal beliefs and utterances. Neither Chomsky’s theory nor GS’s theory are able to cope adequately with the problem, because its nature is strongly elusive to formal rules and its analysis can receive only several ad hoc solutions.